Assessment of Rehabilitation Exercise Monitoring Based on Embedded System - Nimmy John (Current Overview on Disease and Health Research Vol. 3, 2022)
Physiotherapy is essential for the people stricken by the orthopaedic intervention. The intention of the work is to restore the patient’s moving capability by doing exercises. The system developed ensures patient to do physiotherapy exercises in the home. The requirement of the system should be cost operative and user friendly. The system is an easy to use and cost effective for the physically disabled persons. This equipment can be used for finding the range of the movement of the muscle of the patient.